Stories in the flesh: Women in higher education share their tattoos of crucial events, overcoming challenges, and hope - Romero, Christina; Davis, Patricia; Komar, Brooke; Warner, Martha (American Journal of Social Sciences and Humanities, 2025)
Four women in higher education collaborated to share their tattoo stories. In this article of our qualitative research, we use individual journaling and reflections on our tattoo stories, which represent crucial and highly significant experiences. We critically center on findings that emerged from analyzing our stories through the lenses of narrative, intersectionality, attachment theory, continuing bonds, and the exploration of social issues that lie beneath the motives of women permanently memorializing and inking their bodies. Findings relate to tattoo-specific language that reveals cultural and contextual identities related to traumas from our lives.